2010
DOI: 10.1186/1758-2652-13-s4-o51
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the integrase inhibitor S/GSK1349572 in subjects with HIV exhibiting raltegravir resistance: week 24 results of the VIKING study (ING112961)

Abstract: 7‐11 November 2010, Tenth International Congress on Drug Therapy in HIV Infection, Glasgow, UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…RAL blocks the strand-transfer activity of the viral integrase (IN), necessary for the integration of the proviral DNA into the host genome. In addition, other strandtransfer inhibitors are already in clinical studies [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…RAL blocks the strand-transfer activity of the viral integrase (IN), necessary for the integration of the proviral DNA into the host genome. In addition, other strandtransfer inhibitors are already in clinical studies [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The INSTI-resistant patient VIKING pilot study and phase 3 (VIKING-3) study have shown the clinical utility of DTG in patient populations who have failed to respond to INSTI therapy (10,18,19).…”
mentioning
confidence: 99%
“…For example, DTG was shown to have wild-type or near wild-type activity in vitro against site-directed mutants with the single primary resistance mutations observed in vivo at Q148 (including Q148H/K/R), at N155, and at Y143 (25,30) and against clinical isolates harboring genotypes with the Y143 and N155 pathway mutations (46) alone or with additional secondary IN mutations. DTG has also demonstrated in vivo activity in subjects with RAL resistance in the VIKING study (16). As described herein, we investigated the dissociation of DTG, RAL, and ELV from wild-type and mutant IN proteins complexed with DNA to obtain a better understanding of INI dissociation kinetics and the relationship between dissociation rates and INI resistance.…”
mentioning
confidence: 99%